Methodical design process for structural composites to achieve lightweight vehicles. (2017) - Schmidt, Jonathan; Jacobs, Georg; Beger, Anna-Lena; Cadwell, Dave
Integrating as many functions into a part as possible without compromising its main function is a reliable and often applied way to reduce weight when introducing a composite part into a vehicle. By doing so, a significant change of the product architecture (according to Pahl et al. (2013)) is often inevitable. The current price pressure within the automotive industry, however, leads to short development times and, hence, more carry-over parts of previous models and derivatives. To discuss concepts or necessary changes, usually computer aided design (CAD)-models are used. This implies that a high amount of work was already put into the concept development, which is inefficient and expensive for high-level decisions. Thus, a way to allow concept decisions at an early stage of the development is required especially to make the best decision regarding the material selection and to foster material conforming design from the concept phase on.